Studi Karakteristik Mutu Teh Kombucha Rosela Instan Kaya Antioksidan Alami Secara Mikroenkapsulasi - Herla Rusmarilin (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2018)
Kombucha rosella tea is processed from a mixture of traditional black tea and rosella tea using by the "kombucha culture".  To extend the shelf life is made into an encapsulation form. The benefits of kombucha rosela tea is as functional food and has been widely consumed by the community, therefore required a more scientific study. This research consisted of two factors: four rosella tea percentage levels were 20, 40, 60 and 80% with four fermentation time levels of 5, 6, 7 and 8 days, using factorial completely randomized design. The parameters analyzed were moisture content, vitamin C content, total acid, water solubility, tannin content, anthocyanin levels and organoleptic value (colour, flavour and taste). The results showed that the concentration of rosella tea and fermentation time had a significant effect on all parameters. Interactions of the two factors had highly significant effect on total acid and had significant effect on tannin content. Rosella tea concentration of 80%  for 8-days fermentation time resulted in the highest levels of vitamin C of 330.0 mg/100 g, anthocyanin of 348.430 mg / L, tannin content of 2.170% and the best of panel quality.